Gestational Hormone Concentrations Are Associated With Timing of Delivery in a Fetal Sex-Dependent Manner - Cathey, Amber L.; Watkins, Deborah J.; Rosario, Zaira Y.; Vega, Carmen M. Vélez; Mukherjee, Bhramar; O’Neill, Marie S.; Loch-Caruso, Rita; Alshawabkeh, Akram N.; Cordero, José F.; Meeker, John D. (Frontiers in Endocrinology, 2021)
Background: Early delivery remains a significant public health problem that has long-lasting impacts on mother and child. Understanding biological mechanisms underlying timing of labor, including endocrine disruption, can inform prevention efforts. Methods: Gestational hormones were measured among 976 women in PROTECT, a longitudinal birth cohort in Puerto Rico. We evaluated associations between hormone concentrations at 18 and 26 weeks gestation and gestational age at birth, while assessing effect modification by fetal sex. Exploratory analyses assessed binary outcomes of overall preterm birth (PTB, <37 weeks gestation) and the spontaneous PTB subtype, defined as preterm premature rupture of membranes, spontaneous preterm labor, or both. Multivariable logistic and linear regressions were fit using visit-specific hormone concentrations, and fetal sex-specific effects were estimated using interaction terms. Main outcome models were adjusted for maternal age, education, marital status, alcohol consumption, environmental tobacco smoke exposure, and pre-pregnancy body mass index (BMI). Exploratory models adjusted for maternal age and education. Results: We observed reduced gestational age at birth with higher circulating CRH (beta: -2.73 days, 95% CI: -4.97, -0.42), progesterone (beta: -4.90 days, 95% CI: -7.07, -2.73), and fT4 concentrations (beta: -2.73 days, 95% CI: -4.76, -0.70) at 18 weeks specifically among male fetuses. Greater odds of overall and spontaneous PTB were observed among males with higher CRH, estriol, progesterone, total triiodothyronine (T3), and free thyroxine (fT4) concentrations. Greater odds of PTB among females was observed with higher testosterone concentrations. Conclusions: Various associations between hormones and timing of delivery were modified by fetal sex and timing of hormone measurement. Future studies are needed to understand differential mechanisms involved with timing of labor between fetal sexes.